National Security Architecture and the Question of Nigerian Federalism: The Phenomenon of State Police and its Feasibility - Abacha Umar Deribe (UIN Sunan Gunung Djati, 2023)
Nigeria is one of the countries that operates a federal system of government. Likewise, Nigeria has been a federal state with several security challenges for many decades, despite a strong and unified security architecture controlled by the government at its centre. The matters of national security are vested with the central government in the Exclusive List of the Nigerian 1999 Constitution. Despite the huge budget that the Federal Government has allocated towards security operations and operations for many years, there is dissatisfaction and outcries from several segments of the country regarding the current security situation. This study examined the various discourses on redesigning the Nigerian security architecture, including the calls for state police in a fashion that will appease the comprising federating units. The problem is the reservation and the resentment that some stakeholders are expressing towards the decentralisation of the national security architecture. The theory of decentralisation and devolution of powers was adopted in the study. The study utilised documented sources of data, including books, journal articles, newspapers, reports, and internet sources, for data collection. The data obtained were analysed using content analysis, where themes were designed and discussed concerning the adopted theoretical framework. The study discovered that the agitations for state police were perceived by the Federal Government, some state governments, and stakeholders as a political move to weaken the might of the FG and to muster extra powers by some state governors against the public, the opposition, and the FG. The study recommends, among others, that the calls for the decentralisation of national security architecture should not be jettisoned totally as political, but there is a need for caution in establishing them to avoid further security crises in the future because practically, it is not feasible now.